2022
DOI: 10.1155/2022/6741995
|View full text |Cite
|
Sign up to set email alerts
|

Research on the Mechanism of Kaempferol for Treating Senile Osteoporosis by Network Pharmacology and Molecular Docking

Abstract: Kaempferol (KP), as a natural anti-inflammatory compound, has been reported to have curative effects on alleviating senile osteoporosis (SOP), which is an inflammation-related musculoskeletal disease, but the molecular mechanisms remain unclear due to scanty relevant studies. We predicted the targets of KP and SOP, and the common targets of them were subsequently used to carry out PPI analysis. Moreover, we adopted GO and KEGG enrichment analysis and molecular docking to explore potential mechanisms of KP agai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 69 publications
0
5
0
Order By: Relevance
“…They decreased osteoclastogenesis, mainly through RANKL-related pathways, and promoted osteoblast differentiation [ 7 , 52 ]. Proposed mechanisms responsible for the benefits of kaempferol in senile osteoporosis include also anti-inflammatory and antioxidative properties and regulation of osteoblasts' and osteoclasts' apoptosis [ 53 ]. Kaempferol and quercetin in the forms of 3- O -glucuronide, 3- O -galactoside, or O -glucoside were found in small amounts in RED EXT1, but their potential contribution to the antiosteoporotic effect is difficult to elucidate.…”
Section: Resultsmentioning
confidence: 99%
“…They decreased osteoclastogenesis, mainly through RANKL-related pathways, and promoted osteoblast differentiation [ 7 , 52 ]. Proposed mechanisms responsible for the benefits of kaempferol in senile osteoporosis include also anti-inflammatory and antioxidative properties and regulation of osteoblasts' and osteoclasts' apoptosis [ 53 ]. Kaempferol and quercetin in the forms of 3- O -glucuronide, 3- O -galactoside, or O -glucoside were found in small amounts in RED EXT1, but their potential contribution to the antiosteoporotic effect is difficult to elucidate.…”
Section: Resultsmentioning
confidence: 99%
“…3 Some experiments proved that kaempferol can regulate bone metabolism balance and improve bone density by increasing osteoblast activity while decreasing osteoclast activity. [4][5][6][7][8] Our preliminary experiments found that RPN1 may serve as a new target for kaempferol to improve osteoporosis. 9 Therefore, kaempferol which may be a more investigative antiosteoporotic herbal monomer can be used as a complementary and alternative drug with promising clinical applications in the treatment of osteoporosis.…”
Section: Introductionmentioning
confidence: 85%
“…Additionally, the role of Kaempferol in curing senile osteoporosis was also confirmed by performing molecular docking studies. The study revealed that Kaempferol is a potent curative agent against this musculoskeletal disease as it can regulate oxidative stress, various inflammatory pathways, and bone homeostasis [ 250 ]. For the first time, molecular docking investigations performed by Yu X. et al revealed that Naringin might treat osteoporotic fracture, presumably via modulating a variety of signaling pathways and targets associated with the development of osteoclasts and oxidative stress.…”
Section: Discussionmentioning
confidence: 99%